FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA MODAL (Studi pada Pemerintah Kabupaten/Kota Di Jawa Timur) - Fauzia, Farah Wahyu; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to analyze and to examine influence the local own source revenue, balance fund, andsurplusof financing budget to the capital expenditure. Meanwhile the population of this research is all thedistricts or cities in all region of East Java Province, the sampling technique used is purposive sampling, thesample of this study consists of 35 districts or cities in East Java. The research data is the secondary data in theform of Financial Examination Report of districts and cities in East Java Province in 2012-2015 periods. Theresult of the research method is quantitative and the analysis technique has been carried out by using multiplelinear regressions analysis.The result of the research shows that local own source revenue, balance fund, andsurplusof financing budget give positive influence to the capital expenditure. The results of the research supportall hypothesis which have been formulated in this research.Keywords: Local own source revenue, balance fund, surplus of financing budget, capital expenditure.